2020
DOI: 10.31234/osf.io/m59dg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex is a defining feature of neuroimaging phenotypes in major brain disorders

Abstract: Sex differences are found in the incidence and expression of psychiatric and neurodegenerative conditions, and many studies suggest these differences are influenced by innate biological differences between males and females and risk factors that interact with these differences. However, few studies have used neuroimaging to examine brain signatures of disease separately by sex, and many studies of sex differences have been based on small samples and their findings have not been replicated in larger cohorts. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 218 publications
(265 reference statements)
1
4
0
Order By: Relevance
“…Sex differences in other white matter microstructure characteristics – including measures reflecting diffusivity, neurite density, free water, and restriction – depended to a greater extent on the exact region and metric examined. These findings are largely consistent with previous analyses which used DTI or NODDI to assess white matter sex difference (Cox et al, 2016; Jahanshad & Thompson, 2017; Ritchie et al, 2018; Salminen et al, 2020; Toschi et al, 2020); such prior analyses likewise found that males exhibit higher anisotropy and lower fiber dispersion than females, with other microstructure metrics displaying greater variability in their pattern of sex differences. In the current study, we also observed significant sex differences in age effects for a number of regions and microstructure metrics in our cross-sectional sample.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Sex differences in other white matter microstructure characteristics – including measures reflecting diffusivity, neurite density, free water, and restriction – depended to a greater extent on the exact region and metric examined. These findings are largely consistent with previous analyses which used DTI or NODDI to assess white matter sex difference (Cox et al, 2016; Jahanshad & Thompson, 2017; Ritchie et al, 2018; Salminen et al, 2020; Toschi et al, 2020); such prior analyses likewise found that males exhibit higher anisotropy and lower fiber dispersion than females, with other microstructure metrics displaying greater variability in their pattern of sex differences. In the current study, we also observed significant sex differences in age effects for a number of regions and microstructure metrics in our cross-sectional sample.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings expand on this prior work indicating sex differences in age effects among middleaged to older adults. Importantly, a range of neurodegenerative conditions exhibit sex differences in their prevalence and presentation, emphasizing the importance of understanding differences in neural aging between men and women (Salminen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations